Scientists in a laboratory in Leipzig, Germany (1895)
Black and white photograph of scientists standing in a laboratory in Leipzig, Germany. The group of men, many of whom are graduate students studying under Wilhelm Ostwald (1853-1932), surround tables crowded with laboratory equipment, tools, and apparatuses. The scientists pictured from left to right have been identified as Frank B. Kenrick (1874-1951), Samuel Lawrence Bigelow (1870-1947), Julius Tafel (1862-1918), Georg Bredig (1868-1944), Karl Alfred von Zittel (1839-1904), Arthur Rindell (1852-1936), Wilhelm Ostwald (1853-1932), Robert Thomas Diedrich Luther (1868-1945), and, seated in the foreground, Eduard von Stackelberg (1867-1943).
Keywords: Chemists; Ostwald, Wilhelm, 1853-1932; Tafel, Julius; Stackelberg, Eduard von 1867-1943; Bigelow, S. Lawrence (Samuel Lawrence), 1870-1947; Kenrick, Frank B., 1874-1951; Laboratories; Bredig, Georg, 1868-1944; Luther, Robert Thomas Diedrich, 1868-; Zittel, Karl Alfred von, 1839-1904; Rindell, Arthur, 1852-1936; Scientific apparatus and instruments